Corrosion inhibition of mild steel in 1M HCl by D-glucose derivatives of dihydropyrido [2,3-d:6,5-d′] dipyrimidine-2, 4, 6, 8(1H,3H, 5H,7H)-tetraone - Verma C.; Quraishi M.A.; Kluza K.; Makowska-Janusik M.; Olasunkanmi L.O.; Ebenso E.E. (My University, 2025)
D-glucose derivatives of dihydropyrido-[2,3-d:6,5-d′]-dipyrimidine-2, 4, 6, 8(1H,3H, 5H,7H)-tetraone (GPHs) have been synthesized and investigated as corrosion inhibitors for mild steel in 1M HCl solution using gravimetric, electrochemical, surface, quantum chemical calculations and Monte Carlo simulations methods. The order of inhibition efficiencies is GPH-3 > GPH-2 > GPH-1. The results further showed that the inhibitor molecules with electron releasing (-OH, -OCH 3) substituents exhibit higher efficiency than the parent molecule without any substituents. Polarization study suggests that the studied compounds are mixed-type but exhibited predominantly cathodic inhibitive effect. The adsorption of these compounds on mild steel surface obeyed the Langmuir adsorption isotherm. SEM, EDX and AFM analyses were used to confirm the inhibitive actions of the molecules on mild steel surface. Quantum chemical (QC) calculations and Monte Carlo (MC) simulations studies were undertaken to further corroborate the experimental results. © The Author(s) 2017.